Keefektifan Konseling Kognitif Perilaku untuk Mengurangi Kecemasan Siswa dalam Pembelajaran Matematika Secara Daring Sinkronus - Rohmah, Ratna Afiah Awwalu; Hidayah, Nur; Wahyuni, Fitri (Buletin Konseling Inovatif, 2025)
The Covid-19 pandemic is currently sweeping the world in 2020, forcing it to carry out activities remotely and significantly impacting the world of education. This study aimed to determine the effectiveness of behavioural counseling in reducing the anxiety of junior high school students in synchronous mathematics learning during the new normal period of the Covid-19 pandemic. This research is included in quantitative research with experimental methods, and the research design used is one group pretest and posttest design. The research population was students at a junior high school in Malang, Indonesia, who were selected using a purposive sampling technique. Development of an anxiety scale instrument based on Hoeksema theory. The results of this study found that ten students experienced high anxiety. The counseling sessions for the ten students were carried out in 6 meetings. The results of the analysis show that cognitive behavioural counseling is effective in reducing students' anxiety levels in synchronous mathematics learning.